Wynne's war - Gwyn, Aaron (Houghton Mifflin Harcourt, 2014)
"An elite platoon of Special Forces soldiers infiltrates a forbidding Afghan war zone on horseback in search of vast treasure in this lyrical, thrilling blend of military fiction and Western"--